The Relationship Between Academic Stress And Eating Habits In Students Generation Z - Meisa Isna Nursiva; Agil Dhiemitra Aulia Dewi; Nor Eka Noviani (Journal of Food and Culinary, 2026)
Academic stress is a response to academic demands that may affect students’ psychological conditions and eating habits. This study aimed to determine the relationship between academic stress and eating habits among Generation Z university students. A quantitative study with a descriptive-analytic and cross-sectional design was conducted online in Indonesia from March to April 2026. A total of 132 respondents were selected using quota sampling. Academic stress was measured using the Academic Stress Inventory (ASI), while eating habits were assessed using the Adolescent Food Habit Checklist (AFHC). Data were analyzed using descriptive statistics and Fisher’s Exact test. The results showed that all respondents experienced academic stress, with 81.06% categorized as severe and 18.94% as moderate. Severe academic stress was most frequently found among eighth-semester students (40.19%). Most respondents had good eating habits (62.12%), although unhealthy behaviors such as frequent consumption of fried foods and difficulties maintaining a healthy diet were still observed. Statistical analysis showed a significant relationship between academic stress and eating habits among Generation Z students (p = 0.043). These findings indicate that academic stress is associated with eating habits, although the direction of its influence may vary among individuals. Further studies are recommended to examine other factors that may influence eating habits, such as emotional eating, sleep quality, physical activity, and socioeconomic conditions.